2017
DOI: 10.1038/s41598-017-11838-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prognostic, clinical, and renal histopathological characteristics of overlapping idiopathic membranous nephropathy and IgA nephropathy versus idiopathic membranous nephropathy

Abstract: Overlapping idiopathic membranous nephropathy (IMN) and immunoglobulin A nephropathy (IgAN) is rare. This study aims to investigate the unique prognostic, clinical, and renal histopathological characteristics of IMN+IgAN. This retrospective observational study included 73 consecutive cases of IMN+IgAN and 425 cases of IMN treated between September 2006 and November 2015. Prognostic and baseline clinical and histopathological data were compared between the two patient groups. Poor prognostic events included a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
2
19
1
1
Order By: Relevance
“…In total, 506 patients with IMN were identified between 11 September 2006, and 25 November 2015, in The First Affiliated Hospital of Wenzhou Medical University. The diagnostic criteria for IMN and exclusion criteria were same as those used in our previous study [16]. The flowchart detailing the patient selection process is displayed in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 506 patients with IMN were identified between 11 September 2006, and 25 November 2015, in The First Affiliated Hospital of Wenzhou Medical University. The diagnostic criteria for IMN and exclusion criteria were same as those used in our previous study [16]. The flowchart detailing the patient selection process is displayed in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline date for the analysis was the same as the date of biopsy, which also marked the start of the follow-up period. The baseline clinical data and pathological indicators were collected as in our previous study [16].…”
Section: Methodsmentioning
confidence: 99%
“…according to primary diseases, Mn can be categorized into idiopathic membranous nephropathy (iMn) and secondary membranous nephropathy (SMn), while iMn accounts for approximately 80% of the total incidence of Mn (7). in recent years, the morbidity of IMN in China significantly increased from 6.48% between 1997 and 1999 to 22.79% between 2009 and 2011 (8)(9)(10)(11). The clinical prognosis of iMn varies greatly.…”
Section: Introductionmentioning
confidence: 99%
“…The study carried out by Chen et al reported that old age and high blood indices were significantly correlated with poor prognosis of patients with iMN. 24 Therefore, timely and effective treatment and medical care is particularly important for older MN patients.…”
mentioning
confidence: 99%